Epr and Optical Absorption Studies of VO2+ Doped Trisodium Citrate Dihydrate Single Crystals - Karabulut, B; Ilkin, I.; Tapramaz, R (Walter de Gruyter GmbH, 2005)
The electron paramagnetic resonance of VO2+ doped trisodium citrate dihydrate (Na3C6H5O7 center dot 2H(2)O) single crystals and powder has been examined at room temperature. The anaular variation of the EPR spectra has shown that two different VO2+ complexes are located in different chemical environments, each environment containing two magnetically inequivalent VO2+ sites in distinct orientations occupying substitutional positions in the lattice and showing a very large angular dependence. The crystalline field around the VO2+ ion is nearly axial. The optical absorption spectrum shows three bands, centered at 24631, 16892, and 12195 cm(-1). The spin Hamiltonian parameters and the molecular orbital coefficients are calculated from the EPR and optical data, and result are discussed.
Keywords: EPR; Trisodium; Citrate; Absorption the Spectrum; Vanadyl Ion